Funding For Long-term Care Cost: An Analysis Among Malaysian Elderlies In Selangor - Mazlynda Md Yusuf; Sharifah Fairuz Syed Mohamad; Nurin Amni Mohd Arshad; Rose Irnawaty Ibrahim (UPM Press, 2024)
Vol.18 Supp 20